2012
DOI: 10.1016/j.gca.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of CI chondrites: Major and trace elements, and Cu and Zn Isotopes

Abstract: In order to check the heterogeneity of the CI chondrites and determine the average composition of this group of meteorites, we analyzed a series of 6 large chips (weighing between 0.6 and 1.2 g) of Orgueil prepared from 5 different stones. In addition, one sample from each of Ivuna and Alais were analyzed. Although the sizes of the chips used in this study were "large", our results show evidence for minor chemical heterogeneity in Orgueil, particularly for alkali elements and U. After removal of one outlier sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
285
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(318 citation statements)
references
References 50 publications
11
285
0
4
Order By: Relevance
“…Previous studies have demonstrated the utility of Zn isotopes for this purpose. Zn isotopic determinations in chondrites and iron meteorites show significantly more variation than is found in terrestrial materials (Luck et al, 2005;Moynier et al, 2007;Barrat et al, 2012), suggesting volatilization processes and core/mantle segregation in their formation. On the Earth and on the Moon, volatization from impact events is the primary cause of Zn isotopic fractionation (Moynier et al, 2006(Moynier et al, , 2010Albarède et al, 2007;Herzog et al, 2009).…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have demonstrated the utility of Zn isotopes for this purpose. Zn isotopic determinations in chondrites and iron meteorites show significantly more variation than is found in terrestrial materials (Luck et al, 2005;Moynier et al, 2007;Barrat et al, 2012), suggesting volatilization processes and core/mantle segregation in their formation. On the Earth and on the Moon, volatization from impact events is the primary cause of Zn isotopic fractionation (Moynier et al, 2006(Moynier et al, , 2010Albarède et al, 2007;Herzog et al, 2009).…”
Section: Introductionmentioning
confidence: 88%
“…Powders were prepared using a boron-carbide mortar and pestle. Elemental abundances for most of the samples were determined using a high-resolution ICP-MS spectrometer Thermo Element 2 at Institut Universitaire Européen de la Mer (IUEM), Plouzané, following well-established procedures (e.g., Barrat et al, 2012). Results for international standards (BIR1, JB2, WS-E, UB-N, PCC1, Allende powder USNM 3529) have been reported previously (Barrat et al, 2012.…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
“…Based on replicate standards and samples (Barrat et al, 2012, the precision for abundances in powdered samples and residues is much better than 5 %. The precision for trace element ratios (e.g., Eu/Eu*, Tb/Tb*, and Yb/Yb*, where Eu*, Tb* and Yb* are respectively the interpolated Eu, Tb and Yb concentrations for a smooth CI-normalized REE pattern, such that Eu* n =(Sm n x Gd n ) 1/2 , Tb* n =(Gd n x Dy n ) 1/2 and Yb* n =Er n 1/3 x Lu n 2/3 ) is better than 2.5 % (2 x relative standard deviation).…”
Section: Samples and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Figure 6). In contrast to Ba and Hf, which are abundant in the stud- Figure 8 and Table 4 show much enrichment in LREE over the HREE in the analysed samples, [18]; PAAS: post-Archean Australian shale [16]; CI-chondrite, after Barat et al [25]; g-Eu: Eu anomaly; g-Eu = Eu/Eu*; Eu* = (Sm + Gd)/2; g-Eu computed after Tang et al [26]. Values in square brackets are the detection limits for individual oxides.…”
Section: Major Element Geochemistrymentioning
confidence: 88%